Phase constituents, magnetic properties, intergranular exchange interactions and transition temperatures of Ge-doped CeFeB alloys. (September 2019) - Rehman, Sajjad Ur; Jiang, Qingzheng; Liu, Kai; He, Lunke; Ouyang, Han; Zhang, Lili; Wang, Lei; Ma, Shengcan; Zhong, Zhenchen
Abstract: The formation of the paramagnetic CeFe2 phase has deleterious effects on the magnetic properties of CeFeB type alloys. In order to reduce the volume fraction of the CeFe2 phase and improve the magnetic properties of cost efficient CeFeB magnetic alloys, Ce17 Fe77-x Gex B6 (x = 0.0–1.5) alloys were fabricated by melt spinning technique. The crystal structures, magnetic properties, intergranular exchange interactions and phase transition temperatures of CeFe2 and Ce2 Fe14 B phases were investigated. The critical amount of Ge doping enhanced the magnetic properties of the alloys by partially decreasing the formation of paramagnetic CeFe2 phase and refining the nano-grains. The optimized magnetic properties of coercivity Hcj  = 467 kA/m, remanence Br  = 0.51 T and energy density (BH)max  = 40.6 kJ/m 3 were obtained for Ce17 Fe76.4 Ge0.6 B6 alloy. The analysis of Henkel plots confirmed that the exchange interaction among nano-grains was greatly improved for the optimized doping of Ge. The improved magnetic properties of the investigated alloys are attributed to the refined grains, enhanced intergranular exchange interactions and the decrease of paramagnetic phase for the critical amount of Ge. Highlights: Ge was added to CeFeB magnetic alloys fabricated by melt spinning. Ge addition increased the volume fraction of Ce2 Fe14 B phase. Magnetic properties of the alloys were greatly enhanced by a critical amount of Ge. Ge doping enhanced intergranular exchange interactions by refining the nano-grains.